2012
DOI: 10.3892/ijo.2012.1603
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of lymphangiogenesis in human lymphatic endothelial cells by simultaneously blocking VEGF-C and VEGF-D/VEGFR-3 with norcantharidin

Abstract: Lymph node metastasis of tumors is a crucial early step in the metastatic process. Tumor lymphangiogenesis plays an important role in promoting tumor metastasis to regional lymph nodes. Norcantharidin (NCTD) has been reported to possess potent anti-angiogenesis and antitumor properties in several cell lines and xenograft tumor models. However, its role in tumor-associated lymphangiogenesis and lymphatic metastasis remains unclear. Here, we investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 49 publications
2
18
0
Order By: Relevance
“…Cells were cultured to near confluence at 37°C in 35‐mm culture dishes containing DMEM supplemented with 10% FBS. A linear scratch wound was made on the surface of the cultured cells using a sterile blade, according to the scratch wound healing assay (Liu et al, ). Then, the cells on one side of the scratch wound were completely scraped off using a plastic scraper, and the remaining cells were washed with Hank's buffered salt solution.…”
Section: Methodsmentioning
confidence: 99%
“…Cells were cultured to near confluence at 37°C in 35‐mm culture dishes containing DMEM supplemented with 10% FBS. A linear scratch wound was made on the surface of the cultured cells using a sterile blade, according to the scratch wound healing assay (Liu et al, ). Then, the cells on one side of the scratch wound were completely scraped off using a plastic scraper, and the remaining cells were washed with Hank's buffered salt solution.…”
Section: Methodsmentioning
confidence: 99%
“…VEGF-C has received attention as it is one of the most potent growth factors for inducing lymphangiogenesis and promoting lymph node metastasis in a wide range of human malignant tumours. 18,27 However, few data are available regarding the correlation between VEGF-C expression and tumour lymph node recurrence. 30 To our knowledge, the present clinical study is the first to detect VEGF-C mRNA expression in surgically resected pN0 cervical cancer tissues, and to investigate further the role of VEGF-C mRNA expression in relation to clinicopathological factors, lymph node recurrence and prognosis of this disease.…”
Section: Discussionmentioning
confidence: 99%
“…27 The VEGF family is the most widely investigated and most specific regulator of angiogenesis: it consists of six members: VEGF-A, -B, -C, -D, -E and placental growth factor. Among them, VEGF-C and -D are considered to be responsible for tumour lymphangiogenesis and lymph node metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have also shown that the expression of VEGF is significantly related with LNM in cervical cancer . However, the association between the expression of VEGF and LNM in cervical cancer has been reported in several studies, which obtained inconsistent conclusions . Hashimoto et al .…”
Section: Introductionmentioning
confidence: 99%